2016
DOI: 10.1371/journal.pone.0150115
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Rumen Microbial Community Composition during Adaption to an In Vitro System and the Impact of Different Forages

Abstract: This study examined ruminal microbial community composition alterations during initial adaption to and following incubation in a rumen simulation system (Rusitec) using grass or corn silage as substrates. Samples were collected from fermenter liquids at 0, 2, 4, 12, 24, and 48 h and from feed residues at 0, 24, and 48 h after initiation of incubation (period 1) and on day 13 (period 2). Microbial DNA was extracted and real-time qPCR was used to quantify differences in the abundance of protozoa, methanogens, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 55 publications
6
35
0
Order By: Relevance
“…However, bison were fed a forage based diet consisting of barley silage and oats (75:25 DM basis), but even with this difference solid ruminal digesta from bison possessed similar crude protein, NDF and ADF concentrations to that of cattle. Fermenters containing inoculum from both host species were allowed to adapt to the concentrate—straw diet for a period of 8 d, a period that is 6 d longer than the 48 h that have been recently reported to be sufficient to allow microbial populations in the Rusitec to stabilize (Lengowski et al, 2016). Although, there is a possibility that diet may have influenced the nature of the microbial populations within the initial inocula, if it was an overriding factor one would predict that the aNDF disappearance in fermenters inoculated with digesta from cattle should be far higher than those inoculated with bison.…”
Section: Discussionmentioning
confidence: 99%
“…However, bison were fed a forage based diet consisting of barley silage and oats (75:25 DM basis), but even with this difference solid ruminal digesta from bison possessed similar crude protein, NDF and ADF concentrations to that of cattle. Fermenters containing inoculum from both host species were allowed to adapt to the concentrate—straw diet for a period of 8 d, a period that is 6 d longer than the 48 h that have been recently reported to be sufficient to allow microbial populations in the Rusitec to stabilize (Lengowski et al, 2016). Although, there is a possibility that diet may have influenced the nature of the microbial populations within the initial inocula, if it was an overriding factor one would predict that the aNDF disappearance in fermenters inoculated with digesta from cattle should be far higher than those inoculated with bison.…”
Section: Discussionmentioning
confidence: 99%
“…Both of them are run over periods of several days and quantitative and qualitative changes in the microbial populations through the incubation period are therefore likely to occur. Several studies have monitored the shifts in microbial populations in continuous-culture fermenters (Soto et al, 2012 and2013;Martínez-Fernández et al, 2015), but to our knowledge there is only a recent study on this topic in Rusitec fermenters (Lengowski et al, 2016). Lengowski et al (2016) analyzed the changes in microbial populations over the first 48 h of incubation and on day 13, and reported important changes, recommending that the adaptation phase should last longer than 48 h. However, there is little information on the microbial changes occurring between the day 2 and the end of the incubation, and most is limited to protozoal populations (Martínez et al, 2010a and2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have monitored the shifts in microbial populations in continuous-culture fermenters (Soto et al, 2012 and2013;Martínez-Fernández et al, 2015), but to our knowledge there is only a recent study on this topic in Rusitec fermenters (Lengowski et al, 2016). Lengowski et al (2016) analyzed the changes in microbial populations over the first 48 h of incubation and on day 13, and reported important changes, recommending that the adaptation phase should last longer than 48 h. However, there is little information on the microbial changes occurring between the day 2 and the end of the incubation, and most is limited to protozoal populations (Martínez et al, 2010a and2011a). Lengowski et al (2016) reported the effects of forage source (grass v. com silage) on microbial numbers, but the influence of other dietary factors, such as concéntrate level on specific microbial populations has hardly been investigated (Martínez et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fermentation of drought‐stressed M. falcata and T. repens led to significantly different SSCP profiles of Bacteria compared with the control variants. Changes in the substrate type coming along with a different nutrient composition can provoke changes in the microbial population of Bacteria (Lengowski et al, ). Although the chosen experimental approach does not permit conclusions on deviating crude nutrient contents of the drought‐stressed substrates, the results on degradabilities and fermentation characteristics clearly indicate that drought stress must have changed the nutrient availability for the microorganisms in Rusitec.…”
Section: Discussionmentioning
confidence: 99%